Comparative Study of Critical Thinking Skills on PBL Model Learning with Animated Videos between the Students Using Moodle and Google Classroom - Samihah, Ismalida Maftuhatus; Savitri, Erna Noor (Universitas Negeri Semarang, 2021)
This study aims to compare the students’ critical thinking skills who use moodle and google classroom on learning PBL models with animated videos. This is comparative research with a nonequivalent pretest-posttest group design and sampling technique cluster random sampling. Based on the results of the study, it shows that the first experimental class that used moodle is better than the second experimental class that used google classroom. This is obtained from the test results N-gain where the first experimental class obtained a gain score of 0.51 in the fair category, and the second experimental class obtained a gain score of 0.43 in the fair category. The result of t test is t count = 2,8038 > t table = 1,9917 shows that Ha is accepted so that the critical thinking skills of students who use moodle are better than google classroom.